Prospects for the Development of Genealogy in Russia as a Socio-Cultural Institution - M. A. Abramova (Дискурс, 2024)
Introduction. Based on a generalization of approaches to defining the concept of “sociocultural institution” and highlighting its inherent characteristics, in this article the author attempts to identify the status of genealogical research in Russia, which attracts an interest from an increasing number of people.   The main goal and task set by the author is to determine the prospects for the development of genealogical research in Russia and the possibility of transforming its status to the level of a sociocultural institution.   Methodology and sources. The author relies on the works of domestic and foreign researchers on the problem of institutionalization in culture (such as M. Weber, Au. Comte, M. Hauriou, E. Durkheim, P. Sorokin, A.A. Radugin, O.A. Radugina, etc.), on the problems of human satisfaction of values (G. Hegel and K. Marx). The author also used articles and abstracts of dissertations on genealogy from 2000 to 2024, materials of social networks and podcasts: “GEN-TOK”, “History of you & GENTECH”, “Living Book” by I. Bivol, electronic journal “Genealogy for the whole family”, etc., video materials of GENTECH festivals.   Results and discussion. When considering the main features of a sociocultural institution and drawing a parallel with the level of demand for genealogical research, the author focuses on the diversity of meanings in the content of the activities carried out by participants in this process. Summarizing the functions that genealogical research could perform in the formation of spiritual and moral values of society, the author draw the parallel with the provisions of Decree of the President of the Russian Federation of February 28, 2024 N 145 “On the Strategy for Scientific and Technological Development of the Russian Federation”.   Conclusion. The results of the study allowed us to conclude that genealogical research in Russia is currently more of a sociocultural activity, about which we have heard a lot and know little. It has not become a familiar form, and, therefore, in demand and understandable for the majority of Russian families, but it has every chance of becoming not only a factor in their unity and the formation of historical memory, but also a traditional socio-cultural activity that is the norm in society, and not the exception.